Celebrity Endorsement in the Airline Industry of Malaysia - Md Zibran, Ibn Atique (2014)
The practice of celebrities being used for representation services other than performing their actual job as either an actor or an athlete, such as endorsements has proliferated over time. Despite the cost and the risks involved with this technique of advertising, it is been used quite extensively in the present era. Due to the monstrous accessibility of media, the development of another phase of business correspondence has occurred. An increment in the utilization of celebrities in brand message correspondence around both non extravagance brands and extravagance brands has occurred. The instrument of celebrity endorsement has nowadays become a pervasive element in advertising and communication management. Since the late 1930s when Red Cola procured baseball incredible, Babe Ruth to support its soda brand, organizations around the globe have utilized players and big names to advertise their items. Organizations use superstar supports as a component of a whole marking procedure to impart their brands to specific sets of clients. The point when selecting a superstar endorser, an organization should think about the magnetism of the celebrity (regarding physical manifestation, scholarly competencies, ability and lifestyle), the tenability of the celebrity (his or her apparent adroitness and dependability) and the obvious similarity between the celebrity and the brand. It used to be that refreshment organizations, shoe brands, and garments lines were the bread and spread of the celebrity sponsorship circuit. Right away competitors, motion picture stars, and mainstream musical acts are shilling for cell phones in an exertion to cushion their pay. The research aims at investigating airline traveler’s perception towards celebrity endorsed airline.